Assessment of plant-induced suction and its effects on the shear strength of rooted soils. Issue 6 (3rd May 2019) - Yildiz, Anil; Graf, Frank; Rickli, Christian; Springman, Sarah M.
Abstract : Shallow landslides, either on bare or vegetated slopes, can be triggered after a rainfall event due to loss of suction. An extensive laboratory programme was performed in this study to assess the relationships between water content, plant-induced suction, root biomass and shear strength parameters. Root-permeated soils, planted with combinations of different species, were tested in an inclinable large-scale direct shear apparatus. The effects of mycorrhizal fungi were also investigated with inoculated specimens. The results suggested that the root biomass, as well as root/shoot ratio, was an indicator of plant-induced suction and shear strength of root-permeated soils tested under laboratory conditions. Longer plant growth duration and more species yielded higher mean values of matric suction and normalised shear stress. Mycorrhizal fungi were found to be beneficial in improving the plant functions related to water uptake.